Business Feasibility Study Analysis of Dyora Raincoat Bandar Batang - Arafandy, Rayhandika; Abadi, Muhammad Taufiq (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This journal discusses the feasibility analysis of Dyora Raincoat business, a company engaged in the production and sale of raincoats. The purpose of this research is to determine the feasibility of Dyora Raincoat business in terms of finance, market, and management. The research methods used are SWOT analysis and investment feasibility analysis. The survey data indicated that approximately 85% of the respondents regularly use raincoats in their daily activities, indicating a large market for raincoat products in Batang District. The analysis also showed that Dyora Raincoat has great potential for development due to itssignificant market share, outstanding product advantages, and appropriate marketing strategies. However, there are several risks that need to be considered, such as intense competition, high production costs, and fluctuations in raw material prices. Therefore, the company needs to take appropriate measures to address these risks in order to strengthen the feasibility of Dyora Raincoat business in the future